2017
DOI: 10.1080/0142159x.2017.1297530
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of ambiguity, perfectionism and resilience are associated with personality profiles of medical students oriented to rural practice

Abstract: Having a rural background or strong rural interest are associated with a personality profile that indicates a better capacity for coping. Personality may play a part in an individual's interest in rural practice. Rural workforce initiatives through education should encourage and nurture students with a genuine interest in rural practice - regardless of background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Mean scores for each TCI dimension are calculated and ranked: very low (1.00‐1.50), low (1.51‐2.50), average (2.51‐3.50), high (3.51‐4.50) and very high (4.51‐5.00). Previous Australian TCI data of medical and nursing students were compared to this sample . Previous studies indicated the internal reliability (Cronbach alpha) of each dimension ranged from 0.86 to 0.89 for character scales and 0.69 to 0.91 for temperament scales …”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Mean scores for each TCI dimension are calculated and ranked: very low (1.00‐1.50), low (1.51‐2.50), average (2.51‐3.50), high (3.51‐4.50) and very high (4.51‐5.00). Previous Australian TCI data of medical and nursing students were compared to this sample . Previous studies indicated the internal reliability (Cronbach alpha) of each dimension ranged from 0.86 to 0.89 for character scales and 0.69 to 0.91 for temperament scales …”
Section: Methodssupporting
confidence: 87%
“…15,16,25 Previous studies indicated the internal reliability (Cronbach alpha) of each dimension ranged from 0.86 to 0.89 for character scales and 0.69 to 0.91 for temperament scales. 15,16,25 Demographic questions included age, gender, international or domestic student status, marital status, whether the student speaks another language at home, living arrangements and first career preference. Demographics were selected based on a review of the literature and included factors reported to influence students' personality and well-being.…”
Section: R140 Is the 140-item Version Of The Temperament And Charactermentioning
confidence: 99%
“…Registrars training for rural practice may need to be more resilient to succeed in rural communities. 21 Is the situation worse than in the past or simply more overt because of social media exposure? Can resilience be improved through training?…”
Section: Future Needs Of General Practitionersmentioning
confidence: 99%
“…As such, different medical specializations and contexts may potentially be better suited to certain personality traits. Both tolerance of ambiguity and perfectionism are personality traits that vary across all persons, but not frequently researched in the context of medical education and thus are the focus of this study [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%